TEACHING ADULTS AS LEARNERS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This thesis explores effective strategies for teaching adults as learners, focusing on their unique cognitive, motivational, and social characteristics. It examines how interactive methods such as experiential learning, collaborative activities, and technology-enhanced instruction contribute to adult education. The study highlights the importance of creating a learner-centered environment that fosters critical thinking, practical application, and lifelong learning.